Pan‐cancer molecular analysis of EGFR large fragment deletion in the Asian population - Jun Pu; Huannan Guo; Ruoying Yu; Qiuxiang Ou; Hua Bao; Xue Wu; Sanyuan Tang; Qingyong Chang (Cancer Medicine, 2023)
Abstract Background Large fragment deletion (LFD) of EGFR was associated with carcinogenesis in many types of cancers. However, the molecular features of EGFR‐LFD have not been studied in the Asian cancer population. Method Here we retrospectively analyzed the targeted sequencing data from a large cancer database. Results EGFR‐LFD was detected at a frequency of 0.03% with EGFRvIII being the most frequently observed LFD. TERTp variants were identified in 60% of the cases. TP53 alterations (33%) were mutually exclusive with TERTp variants and coexisted with EGFR‐LFD in lung cancer and colorectal cancer. EGFR amplification (67%) and chromosome 10p deletion (53%) were the most focal‐level and arm‐level CNV in this cohort. EGFR exon2–17 skipping was found in the tumor tissue of one patient after progressing on osimertinib. Conclusion Our study provided valuable insights into the distribution and molecular characteristics of EGFR‐LFD, hoping to shed light on the treatment management for EGFR‐LFD carriers.